Gamma radiosensitivity of coffee (Coffea arabica L. var. typica) - Quintana, V. (2019)
The effects of gamma radiation on the germination, survival, and morphological damage in characteristics of the M1 generation of coffee (Coffea arabica L. var. typica) plants was evaluated using seeds collected from Santa Teresa and Chaupimayo, Peru. Under net house, the percentage of germination was 68%, 35%, 10%, and 0% for the Santa Teresa seeds and 75%, 49%, 17% and 0% for the Chaupimayo seeds with irradiation treatments of 0, 50, 100 and 150 Gy, respectively, whereas under laboratory conditions, germination levels were between 70% and 94% across all treatments. The survival rate also decreased with increasing radiation levels, with values of 45%, 32%, 28%, and 10% in the laboratory and 29%, 9%, 6%, and 0% in the net house for the Santa Teresa seeds and 58%, 45%, 38%, and 8% in the laboratory and 42%, 15%, 7%, and 0% in the net house for the Chaupimayo seeds with irradiation treatments of 0, 50, 100, and 150 Gy, respectively. Morphological changes were observed in the plants that survived irradiation at a dose of 100 Gy in terms of the leaf shape, leaf apex shape, young leaf color, plant height, stem diameter, number of leaves per plant, leaf length, leaf width, and distance from the cotyledon to the first node.